2002
DOI: 10.1126/science.1068408
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Chaperones in the Cytosol: from Nascent Chain to Folded Protein

Abstract: Efficient folding of many newly synthesized proteins depends on assistance from molecular chaperones, which serve to prevent protein misfolding and aggregation in the crowded environment of the cell. Nascent chain--binding chaperones, including trigger factor, Hsp70, and prefoldin, stabilize elongating chains on ribosomes in a nonaggregated state. Folding in the cytosol is achieved either on controlled chain release from these factors or after transfer of newly synthesized proteins to downstream chaperones, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
2,344
2
44

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 3,073 publications
(2,410 citation statements)
references
References 84 publications
20
2,344
2
44
Order By: Relevance
“…[19]). Our pathway-focused array contains sequences encoding five of the eight subunits that make up the chaperonin-containing TCP-1 protein (CCT).…”
Section: Chaperonin Subunits Are Upregulated In the Pfc But Downregulmentioning
confidence: 99%
See 1 more Smart Citation
“…[19]). Our pathway-focused array contains sequences encoding five of the eight subunits that make up the chaperonin-containing TCP-1 protein (CCT).…”
Section: Chaperonin Subunits Are Upregulated In the Pfc But Downregulmentioning
confidence: 99%
“…The chaperonin-containing TCP-1 (CCT) is a subclass of the chaperonin protein family that aids in the folding of large nonnative proteins [19,31]. For example, CCT has a hetero-oligomeric structure that helps to create the correct 3-D structure of cytoskeletal proteins such as actin, tubulin and other polypeptides in the cytosol [51].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular chaperones, historically known as heat shock proteins, play important roles in the cellular stress response, also contributing to cellular protein homeostasis under normal conditions through a variety of mechanisms 1, 2, 3, 4. Chaperone activity is underlined by their ability to form interactions with client proteins, as well as other proteins, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Molecular chaperones are also important in regulating the balance between protein synthesis and degradation. 1,2 HSPs have been identified in diverse organisms, ranging from bacteria to humans, and are classified on the basis of their molecular weight. 3,4 The four major groups include HSP110, HSP90, HSP70 and HSP27.…”
mentioning
confidence: 99%
“…HSP90 is ubiquitously expressed in the cytoplasm of normal cells where it binds with many client proteins and is involved in homeostasis. [1][2][3][4][5][6][7] In normal cells, HSP90 is expressed at relatively low levels and does not form complexes with other chaperone proteins. 8 Thus, others have suggested that HSP90 is present in latent form in normal cells.…”
mentioning
confidence: 99%